Composite diaphragm and preparation method and application thereof

CN117878530BActive Publication Date: 2026-10-27ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311637377.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-01
Publication Date
2026-10-27
Estimated Expiration
2043-12-01

AI Technical Summary

Technical Problem

[0005]但是,上述涂层会一定程度降低隔膜的离子电导率,使得隔膜在高倍率充放电中的表现较差,且其安全性的提升也不尽如人意

Benefits of technology

[0012]所述功能层中,PEO是一种结晶性、热塑性的聚合物,具有线型规整的螺旋型结构,具有羟基,可与含有羧基官能团的物质发生氢键结合,在本发明中,作为粘结剂,可将PANI-HNTs粘合成层,同时,其含有羟基官能团可与纤维素基底层形成氢键作用紧密地交联,减小复合隔膜层间的界面阻抗。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004583473040000111
    Figure BDA0004583473040000111
  • Figure BDA0004583473040000121
    Figure BDA0004583473040000121
  • Figure HDA0004583473060000011
    Figure HDA0004583473060000011
Patent Text Reader

Abstract

The application discloses a composite diaphragm and a preparation method and application thereof, and belongs to the technical field of new energy sources.The composite diaphragm comprises a substrate layer and a functional layer which are arranged in a superposed mode.The material of the substrate layer comprises cellulose.The components of the functional layer comprise PANI modified HNTs and PEO.The composite diaphragm can not only improve the safety performance of a lithium secondary battery, but also improve the capacity, the cycle performance and the high-rate working performance of the lithium secondary battery.The application further provides a preparation method and application of the composite diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new energy technology, and in particular to a composite membrane, its preparation method, and its application. Background Technology

[0002] The separator is a crucial component in a battery, preventing short circuits and providing a pathway for the smooth movement of lithium ions. With continuous technological advancements, the demand for safer and more environmentally friendly lithium-ion batteries is increasing.

[0003] Currently, the mainstream separators used in lithium-ion batteries are made of polyolefins. However, polymers shrink at high temperatures and are prone to heat buildup, even leading to explosions, under short-circuit or localized overheating conditions. Therefore, modifying polyolefin separators to improve battery safety is crucial.

[0004] Modification of commercial polyolefin membranes mainly involves coating the surface of polyolefins with polymethyl methacrylate / alumina or polyvinylidene fluoride / alumina, etc., to improve the heat resistance and safety of the membrane through inorganic particles.

[0005] However, the coating mentioned above will reduce the ionic conductivity of the diaphragm to some extent, resulting in poor performance of the diaphragm during high-rate charging and discharging, and its safety improvement is not satisfactory. Summary of the Invention

[0006] The present invention aims to at least solve one of the technical problems existing in the prior art. To this end, the present invention proposes a composite separator that can effectively improve the cycle performance, rate performance, and safety performance of lithium secondary batteries including the composite separator.

[0007] The present invention also provides a method for preparing the above-mentioned composite membrane.

[0008] The present invention also provides a lithium secondary battery comprising the above-described composite separator.

[0009] According to an embodiment of a first aspect of the present invention, a composite membrane is provided, the composite membrane comprising a substrate layer and a functional layer stacked thereon;

[0010] The substrate layer is made of cellulose; the functional layer is composed of PANI-modified HNTs (PANI-HNTs, polyaniline-modified halloysite nanotubes) and PEO (polyethylene oxide).

[0011] The composite membrane according to embodiments of the present invention has at least the following beneficial effects:

[0012] In the functional layer, PEO is a crystalline, thermoplastic polymer with a linearly regular helical structure and hydroxyl groups, which can form hydrogen bonds with substances containing carboxyl functional groups. In this invention, PEO acts as a binder to bond PANI-HNTs into layers. At the same time, its hydroxyl functional groups can form hydrogen bonds with the cellulose substrate layer to tightly crosslink, reducing the interfacial resistance between the composite membrane layers.

[0013] Halloysite nanotubes (HNTs) (Al₂Si₂O₅(OH)₄·2H₂O) possess a nano-hollow multi-walled tube structure, formed by the dislocation and curling of aluminum-oxygen octahedrons and silicon-oxygen tetrahedrons. The inner wall of the tube is an aluminum-oxygen octahedron layer, and the outer wall is a silicon-oxygen tetrahedron layer. The inner surface has Al-OH groups, and the outer surface has O-Si-O groups. Their surface exhibits negative charge over a wide pH range, and these active sites enable the widespread use of halloysite. Halloysite nanotubes share a similar structural morphology with carbon nanotubes (CNTs), and also possess unique and excellent properties such as high aspect ratio, high strength, good corrosion resistance, good thermal conductivity, and high electrical conductivity. This invention utilizes HNTs to prepare functional layers, constructing a lightweight framework (three-dimensional porous coating) that provides rapid ion transport channels, thereby improving ionic conductivity. This provides channels for the rapid and sufficient insertion and extraction of lithium ions by PANI, and further provides conditions for the high redox activity of PANI grown in situ on the HNT surface.

[0014] In addition to conductivity, PANI modified with HNTs also has a certain ability to accommodate active ions such as lithium ions. When the composite separator is used in a lithium secondary battery and the positive electrode of the lithium secondary battery is in contact with the composite layer, the composite separator can not only improve the high-rate performance of the lithium secondary battery, but also increase the capacity of the resulting lithium secondary battery.

[0015] In other words, the functional layer is a three-dimensional porous coating. PANI provides active sites, and HNTs provide fast ion transport channels. It has the ability to conduct lithium ions and electrons, and also has the function of accommodating lithium ions. As a result, the lithium secondary battery including the composite separator can perform high-rate fast charge and discharge, and has high capacity and excellent cycle performance.

[0016] The base layer is made of cellulose, which is an insulating structure. Therefore, the composite membrane formed by the base layer and the functional layer can still have the basic functions of conducting active ions and blocking electrons.

[0017] According to some embodiments of the present invention, in the functional layer, the mass ratio of PEO to PANI-modified HNTs is 1:(1 to 10). For example, it can be approximately 1:3, 1:4, 1:5, 1:8, 1:9, 2:3, or 3:7.

[0018] According to some embodiments of the present invention, the thickness of the composite membrane is 20–35 μm. Specifically, it can be 23–28 μm. More specifically, it can be about 25 μm.

[0019] According to some embodiments of the present invention, in the composite membrane, the thickness ratio of the base layer to the functional layer is 1:(0.5-2).

[0020] According to some embodiments of the present invention, in the composite membrane, the thickness ratio of the base layer to the functional layer is 1:(0.8 to 1.2). For example, it can be approximately 1:1.

[0021] According to an embodiment of a second aspect of the present invention, a method for preparing the composite separator described above is provided, the method comprising the following steps:

[0022] S1. Prepare slurry A, which includes PEO and PANI-modified HNTs;

[0023] Prepare slurry B, which includes cellulose;

[0024] S2. Filter slurry A;

[0025] S3. Add slurry B to the surface of the filter cake formed by slurry A, and continue filtering.

[0026] The preparation method according to embodiments of the present invention has at least the following beneficial effects:

[0027] The preparation method provided by this invention can be achieved by two filtrations combined with simple drying. Compared with traditional extrusion, stretching and other methods, the preparation method provided by this invention is simpler and easier to implement.

[0028] The preparation method provided by the present invention produces a composite separator that can improve the capacity, cycle performance, and rate performance of lithium secondary batteries including the composite separator to a certain extent.

[0029] According to some embodiments of the present invention, in step S1, the method for synthesizing the PANI-modified HNTs includes the following steps:

[0030] D1. Prepare solution A containing acid and aniline;

[0031] Prepare solution B containing the initiator;

[0032] Prepare dispersion C containing HNTs;

[0033] D2. Add solution A and solution B to the dispersion C in sequence, and continue the reaction.

[0034] In the above synthesis process, aniline in solution A polymerizes in situ on the surface of HNTs under the initiation of the initiator in solution B; hydrogen ions from the acid in solution A are doped into polyaniline, improving the conductivity of polyaniline.

[0035] The conductivity of polymers is related to their doping state. Taking PANI as an example, structurally, PANI is a typical conductive polymer. Although it has a strong ability to delocalize π electrons, their mobility is limited in this conjugated system. Only when the conjugated system is large enough does the electron mobility increase, allowing PANI to provide free electrons for conductivity. The relationship between PANI's chemical structure and conductivity is significant. When the degree of oxidation and other conditions are constant, PANI's conductivity is closely related to its doping state. With increasing doping ratio, the conductivity continuously increases, eventually reaching approximately 10 S / cm. When doped with acid, the imine nitrogen atoms in the molecular chain are first protonated. As the acid anion portion leaves, H+... + The electrons are transferred to the PANI molecular chain, causing the nitrogen atoms in the chain to become protonated and positively charged. Thus, after proton acid doping, the electron cloud of PANI rearranges, the quinone ring disappears from the molecular chain, and the positive charge on the nitrogen atom delocalizes, causing the conjugated system to gradually expand and generate free electrons. As a result, PANI exhibits conductivity.

[0036] In other words, in the synthesis method, solution A contains acid, which can dope the obtained polyaniline and significantly improve the conductivity of the HNT-modified polyaniline.

[0037] In step D2 of the preparation method, the order of adding solution A and solution B is specified, thereby avoiding explosive polymerization between solution A and solution B and improving the uniformity of polyaniline deposition on HNTs.

[0038] According to some embodiments of the present invention, in step D1, the HNTs are surface-treated HNTs. Specifically, they are HNTs impregnated with an aqueous solution of dodecyltrimethoxysilane. HNTs are nanoparticles with a certain aspect ratio, but their surface is mainly composed of silicon-oxygen bonds, and the density of hydroxyl groups is low, resulting in weak hydrogen bonding forces. Combined with the effects of size and surface electronic effects, this causes HNTs to aggregate in the matrix, affecting their performance. Pretreatment using the above method can reduce the adhesion difficulty of the PANI obtained in step D2 to the HNTs and improve the uniformity of dispersion.

[0039] According to some embodiments of the present invention, the dodecyltrimethoxysilane aqueous solution is a 93% stock solution diluted to an aqueous solution of 20% to 40%. Using an excess of dodecyltrimethoxysilane ensures the thoroughness of the surface treatment. The surface treatment also includes solid-liquid separation and drying after the impregnation.

[0040] According to some embodiments of the present invention, the number of HNTs is 15 to 30 layers. For example, it can specifically be 20 to 25 layers.

[0041] According to some embodiments of the present invention, the outer diameter of the HNTs is approximately 50 nm.

[0042] According to some embodiments of the present invention, the inner diameter of the HNTs is 15-20 nm.

[0043] According to some embodiments of the present invention, the length of the HNTs is 100–400 nm.

[0044] According to some embodiments of the present invention, in step D1, the volume-to-mass ratio of the acid to aniline is 1 mL: 1.5–2 g. Specifically, it could be approximately 1 mL: 1.8 g.

[0045] According to some embodiments of the present invention, in step D1, the acid includes at least one of hydrochloric acid, sulfosalicylic acid, sulfuric acid, phosphoric acid, and hypochlorous acid.

[0046] According to some embodiments of the present invention, in step D1, the acid is hydrochloric acid. The concentration of the hydrochloric acid is ≥30 wt%. For example, it can be about 37 wt%. More specifically, the molar concentration can be about 12 mol / L.

[0047] According to some embodiments of the present invention, in step D1, the mass-to-volume ratio of aniline to solvent is 0.05–0.1 g:1 mL. Specifically, it can be approximately 0.07 g:1 mL. The solvent of solution A includes water.

[0048] According to some embodiments of the present invention, in step D1, the preparation of solution A is carried out under light-shielding conditions. For example, this can specifically involve wrapping the container used for preparation with tin foil.

[0049] According to some embodiments of the present invention, in step D1, the preparation of solution A includes mixing the aniline and water, and then mixing the resulting mixture with an acid. The mixing time and conditions are not limited, as long as sufficient mass transfer is achieved. For example, the mixing time of the aniline and water is 20–40 min; the mixing time of the resulting mixture and the acid is 10–30 min.

[0050] According to some embodiments of the present invention, in step D1, the initiator includes at least one of ammonium persulfate, hydrogen peroxide, dichromate and persulfate.

[0051] According to some embodiments of the present invention, in step D1, the concentration of the initiator in solution B is 0.1 to 0.2 g / mL. Specifically, it can be about 0.18 g / mL.

[0052] According to some embodiments of the present invention, in step D1, the preparation of solution B includes mixing the initiator and water. The mixing method and duration are not strictly limited, as long as a homogeneous solution is formed. For example, it can specifically be stirring for 30 minutes. The initiator can initiate the polymerization of aniline in solution A on the surface of HNTs.

[0053] According to some embodiments of the present invention, in step D1, the solvent of the dispersion C includes water.

[0054] According to some embodiments of the present invention, in step D1, the solid content of the dispersion C is 25-35 mg / ml. For example, it can be about 30 mg / ml.

[0055] According to some embodiments of the present invention, in step D2, the mass ratio of aniline in solution A to HNTs in dispersion C is 0.4 to 0.6:1.

[0056] According to some embodiments of the present invention, in step D2, the mass ratio of aniline in solution A to initiator in solution B is 1:2 to 3. Specifically, it can be approximately 1:2.5.

[0057] According to some embodiments of the present invention, in step D2, after adding solution A, the dispersion time is 5 to 15 minutes. For example, it can be about 10 minutes.

[0058] According to some embodiments of the present invention, in step D2, the temperature for the continued reaction is 0–5°C. For example, it can be approximately 4°C.

[0059] According to some embodiments of the present invention, in step D2, the duration of the continued reaction is 20 to 30 hours. For example, it can be approximately 24 hours.

[0060] According to some embodiments of the present invention, the synthesis method further includes washing and drying the resulting solid product after step D2. The washing is performed with water to remove unreacted aniline and excess H₂. + The drying method includes baking. The baking temperature is 50–80°C. For example, it can be approximately 60°C.

[0061] According to some embodiments of the present invention, in the slurry A, the mass ratio of PEO to PANI-modified HNTs is 1:1 to 10. For example, it can be about 1:3, 1:4, 1:5, 1:8, 1:9, 2:3 or 3:7.

[0062] According to some embodiments of the present invention, the solid-liquid ratio of slurry A is 1g:30-80mL. Specifically, it can be 1g:45-55mL. The solvent for slurry A is water.

[0063] According to some embodiments of the present invention, the solid-liquid ratio of the slurry B is 1g:30-80mL. Specifically, it can be 1g:45-55mL. The solvent for the slurry B is water.

[0064] According to some embodiments of the present invention, the preparation of slurry B includes grinding the mixture of cellulose and water. The grinding time is 50 to 80 minutes, specifically about 60 minutes. The grinding speed is 1000 to 1500 rpm, specifically 1030 to 1050 rpm. The ball-to-particle ratio is 45:1 to 55:1, specifically about 50:1.

[0065] According to some embodiments of the present invention, in step S2, the filtration method includes vacuum filtration.

[0066] According to some embodiments of the present invention, step S2 further includes a preliminary dewatering treatment after filtration. The preliminary dewatering method for the resulting filter cake is to air dry it along with the filter membrane. The degree of drying is determined by the absence of dripping water and warping of the filter cake. This facilitates subsequent vacuum filtration.

[0067] According to some embodiments of the present invention, step S3 further includes drying the filter cake obtained after the continued filtration. The drying method can be determined according to the conditions available in actual production and is not strictly limited. The continued filtration method includes vacuum filtration.

[0068] In steps S2 to S3, the amount of slurry A or slurry B used for filtration is determined according to the required thickness of each layer in the composite membrane, and there is no uniform limit.

[0069] According to an embodiment of a third aspect of the present invention, an alkali metal secondary battery is provided, the alkali metal secondary battery comprising a cell, the cell comprising a positive electrode, the composite separator and a negative electrode stacked sequentially; wherein the functional layer of the composite separator is in contact with the positive electrode.

[0070] The alkali metal secondary battery provided by the present invention has at least the following beneficial effects:

[0071] Compared with alkali metal secondary batteries including conventional separators, the alkali metal secondary battery provided by this invention has higher discharge capacity, first-time efficiency, and cycle performance, and is more suitable for high-rate charge and discharge; wherein:

[0072] During charging, active ions in the positive electrode migrate to the negative electrode. During discharging, active ions from the negative electrode can not only be embedded in the positive electrode material, but also in the PANI of the composite separator, thereby improving the discharge specific capacity and first efficiency (over 100%) of the alkali metal secondary battery.

[0073] The reversible reaction of PANI in the composite layer during charging and discharging is illustrated below:

[0074] P+A ←→ P+A + +e - ;

[0075] Where P represents PANI and A represents anion. During charging, anions in the electrolyte move towards the positive electrode and undergo an oxidation doping reaction with PANI, which can improve conductivity. Simultaneously, Li... + Other types of alkali metal active ions move towards the negative electrode and are reduced and deposited on the surface of the negative electrode. Electrons flow from the positive electrode into the negative electrode through the external circuit. The discharge state is the reverse process.

[0076] PANI can be represented by a copolymer of quinone diimide and phenylenediamine, with its redox degree represented by the y-value. Different y-values ​​result in different structures, compositions, and electrical conductivities. y=1 represents a fully reduced, all-phenylene structure, while y=0 represents an alternating "benzo-quinone" structure, both of which are insulators. y=0.5 represents a semi-oxidized and reduced structure with a benzo-quinone ratio of 3:1, corresponding to the intrinsic state, i.e., the original state of the polyaniline obtained in this invention, and is green in color; this state changes with charging and discharging. Polyanilines with different oxidation degrees exhibit different compositions, structures, colors, and electrical conductivities. For example, during the transition from a fully reduced state (y=1) to a fully oxidized state (y=0), polyaniline successively changes from yellow, green, dark blue, dark purple, and black with increasing oxidation degree. Due to the change in the PANI oxidation state during charging and discharging, it can be ensured that all layers of the separator are insulating structures under conditions such as full charge and de-charged storage, further improving the safety of alkali metal secondary batteries.

[0077] According to some embodiments of the present invention, the alkali metal secondary battery includes at least one selected from lithium secondary batteries, sodium secondary batteries, and potassium secondary batteries. More specifically, the negative electrode of the alkali metal secondary battery comprises an elemental alkali metal.

[0078] According to some embodiments of the present invention, the alkali metal secondary battery is a fast-charging alkali metal secondary battery.

[0079] According to some embodiments of the present invention, the lithium secondary battery is a fast-charging lithium secondary battery.

[0080] In the lithium secondary battery:

[0081] According to some embodiments of the present invention, the positive electrode active material includes at least one of lithium iron phosphate, lithium cobalt oxide, and lithium nickel cobalt manganese oxide.

[0082] According to some embodiments of the present invention, the negative electrode active material includes at least one of graphite and porous carbon.

[0083] According to some embodiments of the present invention, the lithium secondary battery includes at least one of a half-cell and a full-cell. The half-cell refers to a battery using metallic lithium as the negative electrode active material.

[0084] According to some embodiments of the present invention, the lithium secondary battery includes at least one of button batteries, pouch batteries, cylindrical batteries, and prismatic batteries.

[0085] Unless otherwise specified, the fast-charging alkali metal secondary battery refers to an alkali metal secondary battery that can be charged and discharged at a rate of ≥3C, such as 5C, and maintain good cycle performance.

[0086] When the positive electrode active material is lithium iron phosphate and the negative electrode active material is lithium metal, and the charge / discharge rate is 1C, the lithium secondary battery including the composite separator has a discharge capacity increase of ≥51mAh / g compared to the lithium secondary battery including the conventional separator.

[0087] Unless otherwise specified, the term "about" in this invention actually means that the error is allowed to be within ±2%, for example, about 100 is actually 100 ± 2% × 100.

[0088] Unless otherwise specified, "between" in this invention includes the number itself, for example, "between 2 and 3" includes the endpoint values ​​2 and 3.

[0089] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the invention. Attached Figure Description

[0090] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which:

[0091] Figure 1 This is a schematic diagram of the structure of the composite diaphragm obtained in Embodiment 1 of the present invention.

[0092] Figure 2 This is a partial cross-sectional schematic diagram of the button cell obtained from an application example of the present invention.

[0093] Figure 3 This is a graph showing the rate of return of the button cells from Example 1 and Comparative Example 1.

[0094] Figure 4 This is a schematic diagram of the structure of polyaniline obtained by polymerization in the material preparation example of the present invention.

[0095] Figure label:

[0096] 100. Composite separator; 110. Functional layer; 111. PANI-HNTs; 112. PEO; 120. Substrate layer; 200. Positive electrode; 300. Negative electrode. Detailed Implementation

[0097] The following will describe the concept and technical effects of the present invention clearly and completely with reference to embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.

[0098] In the description of this invention, the terms "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0099] Material Preparation Example 1

[0100] This example synthesizes a PANI-HNTs hybrid material. The specific steps are as follows:

[0101] D1. In a light-protected environment, use a syringe to draw 3.72 g of ANI and add it to a 200 mL beaker. Wrap the beaker with aluminum foil to protect it from light. Place a stir bar in the beaker and add 50 mL of deionized water. Stir on the stirrer for 30 min. Take 2 mL of concentrated hydrochloric acid (37 wt%) and inject it into the beaker. Stir for 20 min to obtain solution A.

[0102] Take another 100mL beaker, weigh 9.12g of ammonium persulfate, add 50mL of deionized water, stir for 30min to dissolve completely, and obtain solution B;

[0103] Take another 100mL beaker, weigh 3g of HNTs, add water and stir for 30min, sonicate for 10min to mix evenly, and obtain a dispersion C with a solid content of about 30mg / mL.

[0104] HNTs were first mixed with an aqueous solution of dodecyltrimethoxysilane before use, followed by solid-liquid separation and drying. The solute in the aqueous solution of dodecyltrimethoxysilane accounted for 27.9% of the solution mass.

[0105] The HNTs used are formed by rolling up more than 20 layers, with an outer diameter of approximately 50 nm, an inner diameter of 15–20 nm, and a length of 100–400 nm. Since a single particle size is unlikely to occur in actual production, the parameters such as inner diameter and length are distributed within the above range.

[0106] D2. Take 20 mL of solution A and add it to dispersion C. Stir for 10 min, then add 20 mL of solution B.

[0107] The above mixture was refrigerated at 4°C for 24 hours; polyaniline was polymerized in situ on the surface of HNTs, and the structure of polyaniline was as follows. Figure 4 As shown.

[0108] D3. Repeatedly centrifuge and rinse the solid product obtained in step D2 with deionized water to remove polyaniline and excess H2O from the surface. + .

[0109] The prepared mixture was dried on a hot table at 60°C and then sealed and stored in a self-sealing bag.

[0110] Material Preparation Example 2

[0111] This example synthesizes a PANI-HNTs hybrid material. The specific steps differ from those in material preparation example 1 in that: in step D2, 20 mL of solution A and 20 mL of solution B are simultaneously added to dispersion C, stirred for 10 min, and then refrigerated using the method described in example 1.

[0112] Material preparation example 3

[0113] This example synthesizes a PANI-HNTs hybrid material. The specific steps differ from those in Material Preparation Example 1 in that:

[0114] In step D1, hydrochloric acid is not added when preparing solution A.

[0115] Example 1

[0116] This example demonstrates the preparation of a composite membrane, with the following specific steps:

[0117] S1. Raw material preparation:

[0118] Preparation of Slurry A (containing PEO and PANI-HNTs):

[0119] First, weigh 0.4g of PEO and pour it into a beaker. Then, weigh 1.6g of PANI-HNTs powder (from Material Preparation Example 1) and add 100mL of deionized water to prepare a mixed slurry of PEO and PANI-HNTs with a solid-liquid ratio of 20mg / mL, which is called slurry A.

[0120] Preparation of pulp B (including cellulose):

[0121] Weigh 2g of cellulose and add 100mL of deionized water to the ball mill jar. Ball mill at a ball-to-material ratio of 50:1 and a speed of 1032r / min for 1 hour. Collect the slurry for later use and call it slurry B.

[0122] S2. Use a vacuum filtration device to filter the membrane with a pore size of 1.2 micrometers. Pour in 20 mL of slurry A to prepare a thin film (functional layer) with a thickness of approximately 12.5 μm. This step focuses on thickness; the amount of slurry A used will vary depending on the size of the membrane.

[0123] S3. After the film obtained in step S2 is dried to semi-dryness (within the time range of no dripping water to no warping), 12 mL of slurry B is poured in and filtered, forming a base layer on one side of the functional layer. The amount of slurry B used in this step follows the same rules as the amount of slurry A used in step S2, and is adjusted according to the area of ​​the resulting composite membrane.

[0124] After drying, a composite separator with a thickness of about 25 μm is obtained. It is then cut into 19 mm diameter round pieces using a slicer (for assembling button batteries; if you want to assemble soft-pack batteries, you need to adjust the cutting size). The pieces are then placed in a self-sealing bag and stored in a desiccator for later use.

[0125] Before using the composite diaphragm, it needs to be dried on a hot table at 100°C for 2 hours to remove residual moisture.

[0126] A schematic diagram of the composite diaphragm 100 obtained in this example is shown below. Figure 1 As shown, it specifically includes a base layer 120 and a functional layer 110 stacked together. The functional layer includes a PEO 112 and PANI-HNTs 111 distributed in the PEO 112.

[0127] Example 2

[0128] This example prepares a composite membrane, which differs from Example 1 in that:

[0129] In this example, the mass ratio of PEO to PANI-HNTs is 1:9 (keeping the sum of their masses constant).

[0130] Example 3

[0131] This example prepares a composite membrane, which differs from Example 1 in that:

[0132] In this example, the mass ratio of PEO to PANI-HNTs is 3:7 (keeping the sum of their masses constant).

[0133] Example 4

[0134] This example prepares a composite membrane, which differs from Example 1 in that:

[0135] In this example, the mass ratio of PEO to PANI-HNTs is 2:3 (keeping the sum of their masses constant).

[0136] Example 5

[0137] This example prepares a composite membrane, which differs from Example 1 in that:

[0138] In this example, the mass ratio of PEO to PANI-HNTs is 1:1 (keeping the sum of their masses constant).

[0139] Example 6

[0140] This example prepares a composite membrane, which differs from Example 1 in that:

[0141] In this example, the mass ratio of PEO to PANI-HNTs is 1:10 (keeping the sum of their masses constant).

[0142] Example 7

[0143] This example prepares a composite membrane, which differs from Example 1 in that:

[0144] In this example, the thickness ratio of the cellulose substrate to the functional layer is 2:1 (keeping the sum of their thicknesses constant at 25 μm).

[0145] Example 8

[0146] This example prepares a composite membrane, which differs from Example 1 in that:

[0147] In this example, the thickness ratio of the cellulose substrate to the functional layer is 1:2 (keeping the sum of their thicknesses constant at 25 μm).

[0148] Example 9

[0149] This example prepares a composite membrane, which differs from Example 1 in that:

[0150] In this example, the thickness of the cellulose substrate and the functional layer is 1:0.8 (keeping the sum of their thicknesses constant at 25 μm).

[0151] Example 10

[0152] This example prepares a composite membrane, which differs from Example 1 in that:

[0153] In this example, the thickness of the cellulose substrate and the functional layer is 1:1.2 (keeping the sum of their thicknesses constant at 25 μm).

[0154] Example 11

[0155] This example prepares a composite membrane, which differs from Example 1 in that:

[0156] In this example, the mass ratio of PEO to PANI-HNTs is 7:3 (keeping the sum of their masses constant).

[0157] Example 12

[0158] This example prepares a composite membrane, which differs from Example 1 in that:

[0159] In this example, the mass ratio of PEO to PANI-HNTs is 1:11 (keeping the sum of their masses constant).

[0160] Comparative Example 1

[0161] This example prepares a diaphragm, which differs from Example 1 in that:

[0162] The resulting membrane consists of two cellulose layers (base layer), without a functional layer, and has the same total thickness as the composite membrane obtained in Example 1.

[0163] The preparation method in this example is the same as that in Example 1, specifically as follows:

[0164] The preparation of slurry A is excluded in step S1; in step S2, 20 mL of slurry A is replaced with 12 mL of slurry B; the rest is the same as the preparation method in Example 1.

[0165] Comparative Example 2

[0166] This example prepares a diaphragm, which differs from Example 1 in that:

[0167] The resulting membrane consists of two functional layers, without a base layer, and has the same total thickness as the composite membrane obtained in Example 1.

[0168] The preparation method in this example is the same as that in Example 1, specifically as follows:

[0169] The preparation of slurry B is excluded in step S1; in step S3, 12 mL of slurry B is replaced with 20 mL of slurry A; the rest is the same as the preparation method in Example 1.

[0170] Comparative Example 3

[0171] This example prepares a diaphragm, which differs from Example 1 in that:

[0172] In slurry A, replace PANI-HNTs with an equal amount of PANI.

[0173] The difference between the preparation method of PANI and the material preparation example is that HNTs are not added to the dispersion C.

[0174] Comparative Example 4

[0175] This example provides a diaphragm, specifically:

[0176] A dispersion comprising PVDF and Al2O3 was coated on the surface of a polyolefin membrane. The mass ratio of PVDF to Al2O3 was 7:3, the base film thickness was 25 μm, and the coating thickness was 3 μm.

[0177] Comparative Example 5

[0178] This example prepares a composite membrane, which differs from Example 1 in that:

[0179] The PANI-HNTs used were from material preparation example 2.

[0180] Comparative Example 6

[0181] This example prepares a composite membrane, which differs from Example 1 in that:

[0182] The PANI-HNTs used were from material preparation example 3.

[0183] Application examples

[0184] This example provides a coin cell battery. The structure of the coin cell battery obtained in this example is as follows: Figure 2 As shown, the button cell includes a positive electrode 200, a composite separator 100, and a negative electrode 300 stacked together; the functional layer 110 of the composite separator 100 faces the positive electrode 200. The negative electrode 300 is made of lithium metal; the positive electrode active material of the positive electrode 200 is lithium iron phosphate.

[0185] Test case

[0186] This example tested the electrochemical performance of the coin cell obtained from the application example. The specific test voltage was 2.5V–4.2V, and the glycemic specific capacity was set at 170 mAh / g. 1C, 3C, and 5C cycle tests were performed. The capacity after the first and 300 cycles at 1C, and the capacity after the first and 100 cycles at 3C and 5C were statistically analyzed. The test results are shown in Tables 1–3. This example also tested the rate performance of the coin cell at 0.05C, 0.2C, 0.5C, 1C, 3C, 5C, 0.5C, and 0.2C.

[0187] Table 1. Capacity of button cells after 300 cycles at 1C.

[0188]

[0189]

[0190] Table 2. Capacity of button cells after 100 cycles at 3C.

[0191] Example 1 167.3mAh / g 165.2mAh / g Example 2 160.3mAh / g 158.1mAh / g Example 3 169.2mAh / g 166.3mAh / g Example 4 163.7mAh / g 163.5mAh / g Example 5 144.1mAh / g 142.9mAh / g Example 6 162.6mAh / g 135mAh / g Example 7 136.7mAh / g 125.6mAh / g Example 8 169.4mAh / g 127.3mAh / g Comparative Example 1 111.8mAh / g 110.6mAh / g Comparative Example 3 127.7mAh / g 124.8mAh / g

[0192] Table 3. Capacity (mAh / g) of coin cells after 100 cycles at different rate levels.

[0193] Example 1 210.6 196.7 182.6 165.2 132.6 Comparative Example 1 158.1 138.6 128.5 110.6 85.3 Comparative Example 3 163.4 155.6 141.4 124.8 109.1

[0194] In the loop results:

[0195] Comparing Example 1 and Comparative Examples 1-3, it can be seen that the composite separator provided by this invention can improve the capacity and cycle performance of lithium secondary batteries in both conventional rate (1C) and high rate (3C) conditions. Specifically, after 300 cycles at 1C, the capacity difference between Example 1 and Comparative Example 1 is >50 mAh / g; after 100 cycles at 5C, the capacity of Example 1 is 132.6 mAh / g, and the capacity of Comparative Example 1 is 85.3 mAh / g. This is mainly because PANI acts as a site for lithium-ion insertion and extraction during charging and discharging, providing additional capacity to the battery, while the remaining structure provides a stable and robust channel for lithium-ion shuttle. If the structure of the composite membrane or the composition of the functional layers in this invention are changed (Comparative Examples 1-3), the electrochemical performance will be degraded, especially the capacity and cycle performance at high rates. For example, in Comparative Example 3, HNTs are not included, so the fast ion channels provided by HNTs are missing, and the cycle performance, especially the cycle performance at high rates, is significantly reduced. For example, in Comparative Example 2, two functional layers are used, but there is no base layer that can isolate electron conduction. Therefore, it cannot objectively function as a membrane, which will lead to a short circuit between the positive and negative electrodes. For safety and other considerations, electrochemical performance testing was not conducted.

[0196] Comparing Examples 1-6 and Examples 11-12, it can be seen that the mass ratio of PEO to PANI-HNTs in the functional layer affects the electrochemical performance of the resulting composite membrane to a certain extent. Specifically, as the proportion of PANI-HNTs increases, the electrochemical performance of the composite membrane shows a trend of first increasing and then decreasing. This is mainly because when the PEO content is too low, the adhesion between the functional layer and the substrate layer, as well as the structural stability of the functional layer, decreases, and PANI-HNTs will fall off. If the PEO content is too high, the amount of substances that can accommodate lithium ions and react with lithium ions in the composite membrane decreases, thus reducing the capacity.

[0197] Comparing Examples 1 and 7-10, it can be seen that when the cellulose substrate is too thin, the composite membrane battery has poor cycle stability. During long cycles, the electronic insulation of the cellulose substrate deteriorates, leading to micro-short circuits in the membrane and thus a decrease in capacity. When the cellulose substrate is too thick, the number of active sites (PANI) in the functional layer decreases, resulting in less additional capacity, which is also not the optimal solution.

[0198] Comparing the results of the comparative examples and Comparative Example 4, it can be seen that, compared with currently commercially available PVDF / AL2O3 coated polyolefin membrane batteries, the composite membrane battery provided by this invention still maintains a capacity of up to 181.6 mAh / g after 300 cycles at 1C rate. This indicates that, compared with conventional commercial membranes, the composite membrane provided by this invention achieves a significant improvement in electrochemical performance.

[0199] Comparing the results of Example 1 and Comparative Example 5, it can be seen that because ammonium persulfate solution B reacts rapidly with aniline solution A, if solution B and solution A are added to solution C at the same time, aniline will not be able to mix fully with HNTs before reacting. As a result, the prepared PANI will agglomerate and be unevenly distributed on the surface of HNTs, affecting the electrochemical performance.

[0200] Comparing the results of Example 1 and Comparative Example 6, it can be seen that the absence of hydrochloric acid in the preparation of PANI-HNTs materials results in low redox properties of the prepared PANI, making it unable to provide Li+. + It provides attachment sites during charging and discharging, thereby affecting electrochemical performance.

[0201] The rate test results show that the composite separator cell provided in Example 1 of this invention still has a discharge specific capacity of 165.2 mAh / g and 132.6 mAh / g respectively after 100 cycles at 3C and 5C rates. This is mainly because PEO swells in the electrolyte, which can provide sufficient lithium ions for high-rate charge and discharge. In contrast, the capacity of the separator formed by multilayer cellulose in Comparative Example 1 is lower than that of Example 1 at all rates. This also shows that the composite separator provided by this invention has the function of improving capacity and is suitable for high-rate charge and discharge (fast charge and fast discharge). Specific test results are as follows: Figure 3 As shown.

[0202] In summary, the composite separator provided by this invention, through structural and compositional design, can improve the capacity and cycle performance of lithium secondary batteries, and is suitable for high-rate charge and discharge. Lithium secondary batteries incorporating the above-mentioned composite separator can be fast-charged and are expected to find wide application in power batteries, energy storage batteries, and batteries for small consumer electronics.

[0203] The embodiments of the present invention have been described in detail above with reference to the accompanying drawings. However, the present invention is not limited to the above embodiments, and various changes can be made within the scope of knowledge possessed by those skilled in the art without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.

Claims

1. A composite diaphragm, characterized in that, The composite diaphragm includes a base layer and a functional layer stacked together. The base layer is made of cellulose; the functional layer is composed of PANI-modified HNTs and PEO. The method for synthesizing PANI-modified HNTs includes the following steps: D1. Prepare solution A containing acid and aniline; Prepare solution B containing the initiator; Prepare dispersion C containing HNTs; D2. Add solution A and solution B to the dispersion C in sequence, and continue the reaction.

2. The composite diaphragm according to claim 1, characterized in that, In the functional layer, the mass ratio of PEO to PANI-modified HNTs is 1:1 to 1:

10.

3. The composite diaphragm according to claim 1, characterized in that, In the composite membrane, the thickness ratio of the base layer to the functional layer is 1:0.5 to 1:

2.

4. The composite diaphragm according to claim 1, characterized in that, The thickness of the composite diaphragm is 20~35μm.

5. A method for preparing a composite separator as described in any one of claims 1 to 4, characterized in that, The preparation method includes the following steps: S1. Prepare slurry A, which includes PEO and PANI-modified HNTs; Prepare slurry B, which includes cellulose; S2. Filter slurry A; S3. Add slurry B to the surface of the filter cake formed by slurry A, and continue filtering.

6. The preparation method according to claim 5, characterized in that, In step D2, the mass ratio of aniline in solution A to HNTs in dispersion C is 0.4:1 to 0.6:1; and / or, in step D1, the volume-to-mass ratio of acid to aniline is 1 mL: 1.5 to 2 g.

7. The preparation method according to claim 5, characterized in that, In step D2, the temperature for the continued reaction is 0~5℃; and / or the duration of the continued reaction is 20~30h.

8. An alkali metal secondary battery, characterized in that, The alkali metal secondary battery includes a cell, the cell comprising a positive electrode, a composite separator as described in any one of claims 1 to 4, and a negative electrode stacked sequentially; in the composite separator, the functional layer is in contact with the positive electrode.

9. The alkali metal secondary battery according to claim 8, characterized in that, The alkali metal secondary battery is a fast-charging alkali metal secondary battery; and / or, the alkali metal secondary battery includes at least one of lithium secondary batteries, sodium secondary batteries, and potassium secondary batteries.

Citation Information

Patent Citations

  • Separator, manufacturing method thereof, and lithium ion secondary cell

    CN104641490A

  • Preparation method for corncob-shaped HNT-PANI / pp

    US20210340323A1